2017
DOI: 10.21276/aabs.2017.1313
|View full text |Cite
|
Sign up to set email alerts
|

A study on prevalence and causative factors of megaloblastic anaemia in Hadoti region.

Abstract: Background: Anaemia is the most common problems encountered by clinicians in Hadoti Region. The affected population includes male, female as well as children. Over the last two decades, it has been found that incidence of megaloblastic anaemia is increasing. Folic Acid and Vitamin B12 deficiency are the most common cause of megaloblastic anemia. Of these two micronutrients, Vitamin B12 deficiency is more common now, due to vegetarian life style of people. At present, Anemia control or prophylaxis program give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…13 A study by Wyckoff KF et al reported subjects with decreased serum vitamin B12 is likely to be without macrocytosis during the period of post fortification and folic acid fortification led to macrocytosis correction related to vitamin B12 insufficiency. 18 Likewise, D'Onofrio et al observed patients with microcytic anemia due to iron deficiency (58 patients) and heterozygous B-thalassemia (40 patients), and macrocytosis (28 patients) all had larger reticulocytes than mature RBCs by 24% to 35%. 22 A study by Balci YI et al claimed that reticulocytes could be the useful marker for differentiating iron deficiency anemia and vitamin B12 deficiency anemia.…”
Section: Resultsmentioning
confidence: 97%
“…13 A study by Wyckoff KF et al reported subjects with decreased serum vitamin B12 is likely to be without macrocytosis during the period of post fortification and folic acid fortification led to macrocytosis correction related to vitamin B12 insufficiency. 18 Likewise, D'Onofrio et al observed patients with microcytic anemia due to iron deficiency (58 patients) and heterozygous B-thalassemia (40 patients), and macrocytosis (28 patients) all had larger reticulocytes than mature RBCs by 24% to 35%. 22 A study by Balci YI et al claimed that reticulocytes could be the useful marker for differentiating iron deficiency anemia and vitamin B12 deficiency anemia.…”
Section: Resultsmentioning
confidence: 97%
“…One of the most common types of anemia is megaloblastic anemia and its incidence has increased over the last 2 decades worldwide. 1 It poses a considerable health problem in developing countries like India and Pakistan and its highest incidence has been reported from India and Africa ranging from 50-71% which is seen more in the younger age group. 2 The main causes of megaloblastic anemia includes vitamin B12 deficiency and folic acid deficiency.…”
Section: Introductionmentioning
confidence: 99%